Opanas Slastyon as a researcher of Sheucenko’s heritage in painting (Pedagogy of Higher and Secondary Education, 2007)
The article gives a broad outline of Slastion's publications investigating Shevchenko’s painting and graphic works. Shevchenko’s paintings are considered to be an indispensable constituent of the process coming into being and developing the art science that deals with particular historic period.
Keywords: Shevchenko's painting and graphic works; the art science at the beginning of the 20-th century; publications on the painter’s heritage in painting